Dimensi Teoretikal Psikoterapi Komplementari dalam Tafsir al-Qurṭubī - Rahim Kamarul Zaman; Khairulnazrin Nasir; Ikmal Adnan (USIM Press, 2024)
Journal of Ma’alimal-Quran wa al-Sunnah Vol. 19, No. 1, Page (96-114)